A cost optimization-based design of precast concrete floors using genetic algorithms - de Albuquerque, Augusto T.; El Debs, Mounir K. [UNESP]; Melo, Antonio M. C. (Elsevier B.V., 2012)
The integrated design optimization, not only the element optimization, is considered a strong trend. The integrated optimization involves the three major stages of an engineering design process namely conceptual design, embodiment design and detailing design. This paper presents an integrated structural precast floor design optimization tool, called DSSPF (Decision Support System for Precast Floors), for precast concrete structures using GA and considers the cost impact at all construction phases like manufacture, transport and erecting in the structural conception. An example indicating the DSSPF results are very consistent with the results of an existing design is further presented. Based on the results obtained, the DSSPF is considered a powerful novel tool to assist designers in the choice of structural layout and initial element dimensioning phases. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Structural optimization; Precast concrete; Genetic algorithm